Cultivating Positive Youth Development, Critical Consciousness, and Authentic Care in Urban Environmental Education - Delia, Jesse; Krasny, Marianne E. (Frontiers in Psychology, 2018)
This paper addresses the issue of how to provide affordances for youth development in the context of environmental stewardship in cities. Urban environmental education encompasses place-based and action-oriented stewardship practices, including community gardening and vegetable production, often with the dual goals of developing youth and community assets. Yet in-depth understanding of how these goals are achieved is lacking. Using narrative inquiry, we explored participant experiences in a multi-year agriculture internship program conducted by the food justice organization East New York Farms! (ENYF) in Brooklyn, NY. Emerging from our conversations with youth were five themes defining their intern experience: ENYF as somewhere to belong, to be pushed, to grapple with complexity, to practice leadership, and to become yourself. We propose a theory of change that emphasizes politicized notions of caring as a foundation for cultivating developmental assets, including competence, contribution, and critical consciousness, among youth who participate in ENYF programs multiple years. This paper extends the literature on socio-environmental affordances to encompass urban environmental education programs, which incorporate physical and social features that act as affordances. Further, this paper describes a feedback loop in which youth afforded opportunities to develop assets through contributing to their community in turn create affordances for additional youth and adults.